‘Bright Lights and Dark Knights’: Racial Publics and the Juridical Mourning of Gun Violence in Toronto - H.V. B. Buffam (Law Text Culture, 2009)
On 26 December 2005, 15-year-old Jane Creba was killed by gunfire that erupted between two groups of young men in the central consumer district of Toronto. This article examines how the public mourning of this white high school student is routed through racial knowledges of criminality that invest her death with an affective ‘public’ significance in contradistinction to the other victims of gun violence in 2005, most of who were young African Canadian men reputed to participate in gangs. By explicating the racial modes of publicity that are borne of this event, this article illustrates how the mediated circulation of this crime scene works to articulate phantasmic geographies of segregation atop the more convivial forms of sociality that characterize life in the city. It then shows how ‘black’ gun violence is configured as a force exogenous to consumer spaces, warranting the use of legal technologies of the state to (re)establish the racial boundaries of the city. The article concludes by gesturing to the possibility of innovating modes of publicity that can resist and subvert the logic and affective force of racial knowledges that otherwise structure the mediation of crime.